WORD AND PHRASES TRANSLATION PROCEDURES USED IN THE INDONESIAN SUBTITLE OF TED-ED YOUTUBE VIDEOS - Fadhil Asyrafi (Universitas Jambi, 2020)
This study identifies the translation procedures used in Indonesian subtitles of TED-Ed YouTube education videos in the level of nouns or noun phrases. This research used descriptive qualitative method where the researcher listed and identified the procedures found and described each of them according to the theory of Newmark (1988, p. 81-93). The objects and the sources of data in this research are only two videos in the channel specifically selected by the researcher, focusing on one translator with most contributions to the TED-Ed Indonesian community as of August 2019: Dewi Barnas. The subtitles are then downloaded and analyzed. The first video (The loathsome, lethal mosquito) has 32 noun phrases belonging to specific translation procedures, whereas the second video (The benefits of a bilingual brain) has 80 noun phrases translated that way. Some procedures that appear quite often are: Naturalization, Transference, Expansion, Reduction, Synonymy, Functional Equivalent, Paraphrase and Transposition.